The Effect of Thin Capitalization and Accounting Conservatism on Tax Planning with Profit Quality as a Moderating Variable in Industrial Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2021 Period - Arum, Diffa Sekar; Mulyadi, Mulyadi; Sianipar, Panata Bangar Hasioan (Nexus Synergy: A Business Perspective, 2023)
The purpose of this study was to examine the effect of thin capitalization and accounting conservatism on tax planning, both directly and through the earnings quality variable as a moderation. The research method used in this study is a quantitative research method with the type of data, namely secondary data, obtained from published financial reports. The population and sample used in this study are the annual financial reports of industrial sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period using the sample selection technique, namely the purposive sampling technique. The results of the study reveal that thin capitalization has an effect on tax planning, accounting conservatism has no effect on tax planning, earnings quality moderates the effect of thin capitalization on tax planning, and earnings quality moderates the effect of accounting conservatism on tax planning.